The Effectiveness of CBT Group Counseling with a Cognitive Restructuring Technique to Reduce Students’ Smartphone Usage Problems - Fitriana, Mar'ah; Eddy Wibowo, Mungin; Purwanto, Edy (Universitas Negeri Semarang, 2023)
Smartphone usage problems contribute negative impacts on students’ physical and psychological development. Thus, the present study attempted to determine the effectiveness of CBT group counseling with a cognitive restructuring technique to reduce students’ smartphone usage problems through a randomized pretest-posttest control group design. This intervention was given to the experimental group, while the control group received the conventional counseling. Further, students’ data were collected using a smartphone addiction scale (SAS) whose reliability was 0.95 and was adapted using scientific procedures. Once the data collected, Wilcoxon signed rank and Mann-Whitney U tests were carried out. Findings showed that the CBT group counseling with a cognitive restructuring technique implemented gained more effective than that of conventional in the control group. Based on this finding, this study contributes to the improvement of a guidance and counseling service quality in terms of the use of CBT group counseling with a cognitive restructuring technique to reduce students’ smartphone usage problems